South Asian Economic Integration and Institution Building: Some Insights from EU Experience - Chauhan, Pradeep S (Economic Journal of Nepal, 2011)
Does the integration of markets for goods. services and capital drive the creation of regional institutions? Or, does the creation of regional institutions drive the integration of markers? The short answer is that the relationship is reciprocal but not deterministic; it varies across regions and is conditioned by several contextual factors. This paper examines the reciprocal relationship between economic integration and institutional integration. The paper addresses key factors that affect the political dynamic between markets and institutions - such as political regionalism. multilateralism and private networks - and derives some lessons front the European experience for institutions in other regions. The paper concludes that aspirations for political union are not a necessary precondition for building regional institutions that foster economic integration. Strengths and weaknesses of multilateral economic institutions provide critical explanations for regionalism: and regions should pay due regard to the multilateral regime when designing their institutions and collective practices. The paper tried to compare different regions including Asia. Key words: Economic Integration; Institutional integration; Political regionalism Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 31, No. 4 October-December 2008, Issue No. 124 Page: 193-211 Uploaded date: 5 July 2011